Reflection on a professional advisory group to inform the use of patient empowerment tools within an implementation science research project - Katherine E. Woolley; Nia J. Jones; Robert Letchford; Kathleen L. Withers (Journal of Patient-Reported Outcomes)
Abstract Professional advisory groups, with patient and public involvement (PPI) representatives, can be used for co-production within research projects. This paper aims to document the benefits and challenges of undertaking stakeholder and participant engagement for an implementation research project within NHS (National Health Service) Wales. A patient focused research project, initiated by clinicians, on the use of patient empowerment tools within standard patient care, used a professional advisory group to identify appropriate tools to use within the research proposal. The professional advisory group was made up of therapists, NHS stakeholders, academics and PPI representatives. A hybrid-meeting style was employed to optimise participation for all members of the group. Benefits of the professional advisory group included increased engagement and ownership of the study due to co-creation, and obtaining important contextual information and lived experience. However, challenges included keeping the discussion on topic due to pre-conceived agendas, pleasing everyone in the room due to varied backgrounds, and technological issues. Future professional advisory groups should consider how to facilitate the full involvement of PPI representatives within the discussion and having a variety of resources to present the topic of discussion. Furthermore, clearly communicating what the purpose and direction of the research project is and how it fits into the wider system, should be carefully considered. Overall, it was recognised that the professional advisory group was of significant value to shape the research proposal. Due to the situational challenges faced by healthcare professional within the NHS and preconceived ideas for solutions, it is hoped that by involving stakeholders early in the process there will be greater acceptance and usability of the research findings.